2013
DOI: 10.1063/1.4781089
|View full text |Cite
|
Sign up to set email alerts
|

A biomass briquetting fuel machine and its large-scale operation system

Abstract: Biomass such as agricultural and forestry residues is an important resource for energy. Biomass can be converted into densified solid biofuel by briquetting fuel technology to increase the number of applications and enhance its utilization efficiency. In this study, a flat die press machine was designed and studied to realize characteristics of a broad range of feedstock, variable briquetting diameter and length, high briquetting efficiency, easy process control, low processing noise, and low energy consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…In the screw extruder, which requires a heated matrix to reduce friction, the biomass is continuously extruded by a screw through a conical matrix. Although piston presses consume less energy in their execution and cause less wear on the contact parts, screw press machines deliver briquettes of superior quality [55,56]. Some of the main briquette production machines can be seen in Table 1.…”
Section: Main Briquette Production Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the screw extruder, which requires a heated matrix to reduce friction, the biomass is continuously extruded by a screw through a conical matrix. Although piston presses consume less energy in their execution and cause less wear on the contact parts, screw press machines deliver briquettes of superior quality [55,56]. Some of the main briquette production machines can be seen in Table 1.…”
Section: Main Briquette Production Processesmentioning
confidence: 99%
“…Based on the occurrence between the works, it is observed that the most used input parameters for the production of briquettes are the briquetting temperature, the proportion of biomass mixture, presence of binder, pressing time of the briquettes during its production, moisture content of raw material before briquetting, compaction pressure and material granulometry. Since the production of briquettes consists of the densification of loose particles of solid material in a high-density fuel [10,56], it is necessary that operational factors, such as pressure, temperature and compaction time are defined for the production of the briquettes. As the definition itself suggests, biomass must initially be in the form of loose particles, preferably classified according to their size and distribution, being one of the most important material parameters for the densification process [13,41].…”
Section: Main Parameters Of Briquette Production In Academic Workmentioning
confidence: 99%
“…Problems related to the disposal of agricultural and industrial biomass wastes can in part be addressed through their use as biomass fuel, in forms like briquettes . If produced at low cost and made conveniently accessible to consumers, biomass briquettes can serve as complements to firewood, charcoal, and kerosene for domestic cooking and agroindustrial operations, thereby reducing the high demand for other fuels . Briquettes have many advantages over conventional firewood, including higher heat content, ease of use, cleanliness, and compact size.…”
Section: Introductionmentioning
confidence: 99%
“…[8] If produced at low cost and made conveniently accessible to consumers, biomass briquettes can serve as complements to firewood, charcoal, and kerosene for domestic cooking and agroindustrial operations, thereby reducing the high demand for other fuels. [9,10] Briquettes have many advantages over conventional firewood, including higher heat content, ease of use, cleanliness, and compact size. The latter reduces the need of storage space and makes transport more affordable and less resource intensive.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, research into alternative energy sources has become popular over the past decade, with many scientists focused on renewable energy sources with low carbon emissions and minimal environmental impact. These include solar energy [ 1 , 2 ], geothermal heat [ 3 , 4 ], tides [ 5 ], and various forms of biomass [ 6 , 7 ]. Photocatalytic water splitting, as the most direct method for achieving the goal of clean and renewable energy [ 8 ], is also the most investigated method of directly converting solar energy into chemical energy.…”
Section: Introductionmentioning
confidence: 99%